2019
DOI: 10.2144/fsoa-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Long Lasting Response of Trabectedin in Patient With Gastric Leiomyosarcoma With Liver Metastasis: an Update to Previous Report

Abstract: Leiomyosarcoma of the stomach is an extremely rare malignancy for which treatment in advanced disease is hardly reported. Here, we report a case of a 48-year-old man with metastatic gastric Leiomyosarcoma who had previously received a combination of gemcitabine and docetaxel followed by pazopanib after detection of metastasis. The patient was started on trabectedin as per protocol and had disease control continuing for 17 cycles of trabectedin. His quality of life and absence of significant toxicities highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The data on trabectedin is sparse from developing countries with occasional case reports. 26 There is a need of collaborative studies from the developing world.…”
Section: Discussionmentioning
confidence: 99%
“…The data on trabectedin is sparse from developing countries with occasional case reports. 26 There is a need of collaborative studies from the developing world.…”
Section: Discussionmentioning
confidence: 99%
“…On occasion excision, radiation or ablation of under-responding metastases can allow this. A number of investigators have now reported long treatment times with disease stability utilizing trabectedin [ 1 - 3 ]. This case report represents a patient with a prolonged treatment time on trabectedin.…”
Section: Introductionmentioning
confidence: 99%
“…Leiomyosarcoma (LMS) represents about 1% of primary malignancies of the stomach, evolves with hepatic implants in 2-thirds of cases, and the outcome is often poor [1][2][3][4][5][6][7]. Immunosuppression, Epstein-Barr virus, chemicals, and radiation can be related factors [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Spindle cells of the muscularis propria or muscularis mucosa present high proliferation rates and positivity for desmin, a-muscle-specific actin, and vimentin [2,3,6]. Although immunohistochemical findings can avoid pitfalls with other gastrointestinal tumors, the diagnosis often occurs at late stages because of the insidious clinical course [2][3][4][5][6][7]. LMS predominantly affects female adults (5:3) and the sixth decade of life, pain occurs in near 75% of patients and the control is very difficult in most of them [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation